Conjecturing via Analogical Reasoning in Developing Scientific Approach in Junior High School Students. (February 2016) - Supratman,; Ryane, S; Rustina, R
Abstract: This study aims to explore the extent to which the use of analogy reasoning when students conduct conjecture in developing the scientific approach, so that the knowledge of the students can be used to build new knowledge. Analysis was conducted on student learning outcomes in Ciamis district. Based on these results, it was found the teacher not give an opportunity to the students to make conjecture on the students in problem solving as well as the construction of new knowledge. Moreover, teachers do not take advantage of analogical reasoning and scientific approach in constructing new knowledge.